Molecular diagnostics of myeloproliferative neoplasms - Langabeer, Stephen E; Andrikovics, Hajnalka; Asp, Julia; Bellosillo, Beatriz; Carillo, Serge; Haslam, Karl; Kjaer, Lasse; Lippert, Eric; Mansier, Olivier; Oppliger Leibundgut, Elisabeth; Percy, Melanie J; Porret, Naomi; et al. (European journal of haematology, 2015)
Since the discovery of the JAK2 V617F mutation in the majority of the myeloproliferative neoplasms (MPN) of polycythemia vera, essential thrombocythemia and primary myelofibrosis ten years ago, further MPN-specific mutational events, notably in JAK2 exon 12, MPL exon 10 and CALR exon 9 have been identified. These discoveries have been rapidly incorporated into evolving molecular diagnostic algorithms. Whilst many of these mutations appear to have prognostic implications, establishing MPN diagnosis is of immediate clinical importance with selection, implementation and the continual evaluation of the appropriate laboratory methodology to achieve this diagnosis similarly vital. The advantages and limitations of these approaches in identifying and quantitating the common MPN-associated mutations are considered herein with particular regard to their clinical utility. The evolution of molecular diagnostic applications and platforms has occurred in parallel with the discovery of MPN-associated mutations, and it therefore appears likely that emerging technologies such as next-generation sequencing and digital PCR will in the future play an increasing role in the molecular diagnosis of MPN.
Keywords: exony; mutace; essential thrombocythemia; Exons; Janus kinasa 2; receptory thrombopoetinu; Receptors, Thrombopoietin; kalretikulin; Janus Kinase 2; Molecular Diagnostic Techniques; primary myelofibrosis; MPL; zajištění kvality zdravotní péče; Calreticulin; diagnostické techniky molekulární; CALR; Myeloproliferative Disorders; lidé; JAK2; Humans; myeloproliferativní poruchy; polycythemia vera; Quality Assurance, Health Care; myeloproliferative neoplasms; Mutation; molecular diagnostics